2009
DOI: 10.1177/1461444809340786
|View full text |Cite
|
Sign up to set email alerts
|

‘It could be useful, but not for me at the moment’: older people, internet access and e-public service provision

Abstract: Older people are commonly constructed as a group of heavy users of public services that misses out on opportunities presented online, mainly due to age-related barriers to accessing the internet. Drawing on a study of internet access in sheltered homes for older people, this article argues for the need to focus electronic service provision around the needs, preferences and abilities of the users of public services. A user-centred perspective in e-government and e-service provision requires an understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 23 publications
1
75
0
11
Order By: Relevance
“…When it comes to media use in everyday life, older adults are often regarded as lacking media competences when they are presented in popular media discourse, at the policy level and in research (Schreurs & Quan-Haase, 2017;Sourbati, 2009;Wandke, Sengpiel, & Sönksen, 2012). While statistics show that older adults are the most prominent users of print newspapers, radio and television compared to other age groups (see for instance European Commission, 2015), the competences that they are seen as lacking are "new media" skills.…”
Section: Growing Old With Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to media use in everyday life, older adults are often regarded as lacking media competences when they are presented in popular media discourse, at the policy level and in research (Schreurs & Quan-Haase, 2017;Sourbati, 2009;Wandke, Sengpiel, & Sönksen, 2012). While statistics show that older adults are the most prominent users of print newspapers, radio and television compared to other age groups (see for instance European Commission, 2015), the competences that they are seen as lacking are "new media" skills.…”
Section: Growing Old With Mediamentioning
confidence: 99%
“…Blaakilde, Iversen & Wilin ´ ska Editorial: Growing old with and via media Notably, much research assumes that the use of digital media will be highly benefi cial for older adults but fails to examine the issue from the point of view of older adults themselves (Sourbati, 2009). On one hand, there may be many good reasons why the very old are often hesitant to adopt emerging and new technologies into their lives (Hagberg, 2012).…”
Section: Growing Old With Mediamentioning
confidence: 99%
“…Conversely, we also found concern expressed that older adult patients may overestimate their capability: "Father would be completely unable to use technology, but would think that he could"-Carer of patient aged 75+. Sourbati [12] found that in general older people had very little idea how online services might benefit them.…”
Section: Qualitative Feedback: Attitudinal Factorsmentioning
confidence: 99%
“…There could be no confidence that messages etc would be picked up." -MATS Carer, [55][56][57][58][59][60][61][62][63][64] It is recognised that if users are unwilling or simply uninterested in using digital technology, then they will not integrate it into their daily routines [12] . Conversely, we also found concern expressed that older adult patients may overestimate their capability: "Father would be completely unable to use technology, but would think that he could"-Carer of patient aged 75+.…”
Section: Qualitative Feedback: Attitudinal Factorsmentioning
confidence: 99%
“…Seniors are also more likely than any other age group to be living with some kind of disability, which could hinder their capacity to get to a computer training center or read the small type on many Web sites (Fox, 2004). Sourbati (2009) clarifies the reasons related to disability, saying that a decline in vision, slowing of movement and arthritis-related physical dexterity make it difficult to use technological artifacts designed for younger, able-bodied users. Declines in perceptual and cognitive abilities can also impede their ability to learn to use new ICTs.…”
Section: Age and Digital Exclusionmentioning
confidence: 99%